Singapore : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2013)
This paper discusses key findings of the Financial System Stability Assessment on Singapore. The Singapore financial system is highly developed, and well regulated and supervised. Singapore's current regulation and supervision are among the best globally. The Monetary Authority of Singapore (MAS) oversees the entire financial system, and has the analytical and operational capabilities to do so effectively. Singapore is exposed to a broad array of domestic and global risks, especially in light of its interconnectedness with other financial centers. Stress tests suggest that these risks are manageable. This reflects the decisive macroprudential actions taken by MAS to address the threat of a bubble in the housing sector.